Use of surgical mesh of different compositions in the correction of the abdominal wall defect in rats - Isa,Ana Cristina (2015)
Objective: To analyze the performance of two surgical meshes of different compositions during the defect healing process of the abdominal wall of rats. Methods: thirty-three adult Wistar rats were anesthetized and subjected to removal of an area of 1.5 cm x 2 cm of the anterior abdominal wall, except for the skin; 17 animals had the defect corrected by edge-to-edge surgical suture of a mesh made of polypropylene + poliglecaprone (Group U - UltraproTM); 16 animals had the defect corrected with a surgical mesh made of polypropylene + polidioxanone + cellulose (Group P - ProceedTM). Each group was divided into two subgroups, according to the euthanasia moment (seven days or 28 days after the operation). Parameters analyzed were macroscopic (adherence), microscopic (quantification of mature and immature collagen) and tensiometric (maximum tension and maximum rupture strength). Results : there was an increase in collagen type I in the ProceedTM group from seven to 28 days, p = 0.047. Also, there was an increase in the rupture tension on both groups when comparing the two periods. There was a lower rupture tension and tissue deformity with ProceedTM mesh in seven days, becoming equal at day 28. Conclusion : the meshes retain similarities in the final result and more studies with larger numbers of animals must be carried for better assessment.